A experiência total no romance-reportagem: uma estratégia ético-estética - Borges, Luana Silva (2022)
This research, carried out in the Graduate Program in Communication at the Federal University of Goiás, brought two distinct and complementary fields into dialogue: Journalism and Literature. In this hybridism, the practice of in-depth reporting was analyzed in the light of the Theory of Novel. It was shown that neither the novelistic text nor the journalistic text is sustained without the truth and, therefore, contrary to the fear about the imbrication between the genres, it was understood that both have more similarities than divergences. The novel is usually made of intimate contact with unfinished reality; an approach to the reader's psyche; a staging of the plurality of voices expressed in everyday life; of a vivification of the bewilderment of sometimes silent characters. The novelized reportage, in turn, is also made up of the same terms: there is an intimacy with what is to come today and, moreover, an ability to approach the minds that devour it. From these biases, the thesis expressed here was that the novelization of the report is constituted as a strategy not only related to textual architecture or the arrangement of language. More than a writing technique, this thesis argued that novelization refers to an ethics of journalistic coverage, especially when the investigation concerns themes that are situated on the limit of language. In order to defend this point of view, an essay analysis of two reports was constructed: Los suicidas del fin del mundo – chronicles of a patagónico pueblo (2005), by the Argentine journalist Leila Guerriero; and Every day the same night – the untold story of Nightclub Kiss (2018), by Brazilian Daniela Arbex. Guerriero went to Las Heras, a small town in Argentine Patagonia, to investigate a wave of suicides that, between 1997 and 1999, devastated dozens of young people who lived there. Arbex went to Santa Maria, in Rio Grande do Sul, facing mothers and fathers who lost their children to the fire at the Kiss nightclub. These investigations tried to reach the silence of the abrupt loss, at first, and then the attempt, on the part of the family and friends of those who passed away, to understand the totality of life with its setbacks. Thus, as the factual domain is insufficient to deal with these themes, it was found that the reporters romanticized their narratives. As verified in this research, the novel was constituted as the genre most used to this kind of supply, at the same time, of a total experience and of a bewilderment – ​​silent and wandering. It was concluded that, in the face of such complex themes, the authors put the novel into action to vivify, in the reader's eye, and via formal realism, space, time and the progressive, felt discoveries of the characters. The novel-report amalgam composed an ethics based on respect for otherness, since, through the novel-form, the reader had the possibility of diving into the world of others, living it closely and, for that very reason, recognizing it in Himself, without judging him or without transforming the events of this alien life into mere fait divers. Methodologically, the novels-reports were considered not as simple objects of study, but as articulators of experiences that carry times and places full of the tensions of historical reality. Finally, in the movement of the journalistic fabric towards the novelistic possibilities, it was noticed that the coverage can, in fact, be enhanced: they will amplify towards themes that, without the possibilities of the Romance, would be inaudible or taboos in the routines of the press traditional.